Recent important insight into nutraceuticals potential of pigmented rice cultivars: A promising ingredient for future food - Loan, Le Thi Kim; Vinh, Bui The; Tai, Ngo Van (My University, 2024)
Many phytochemicals and nutraceuticals have historically been known to have positive effects on health, especially in ancient and modern health systems. Due to the presence of color, rice, a common basic meal, has anti-inflammatory, anti-cancer, and nutritional effects. It has been shown that polyphenols in rice extracts can alter important signaling pathways involved in cancer. It is also commonly used for its nutritional benefits and to promote general health. We cover the phytochemicals and potential health benefits of colored rice in this brief review. This article discusses the relatively limited in vivo research that has been done to date to formally establish the nutritional potential of rice. Importantly, the available literature supports and promotes the use of colored rice as an anti-diabetic agent, source of prebiotics, and cancer-preventing agent. To methodically evaluate the clinical efficacy and potential of colored rice, future research must focus on properly planned clinical trials in cancer and diabetes patients. Further scientific research on rice extract alone or colored rice flour as a nutritional food and/or functional food could pave the way for new ways to explore the health benefits of rice from experiment to the clinic to prevent disease.
Keywords: Antioxidant; Color; Healthy; Nutraceutical; Rice